Maternal Nutrition Program in Nepal. - Paudyal, Naveen. (Tufts University. Tisch Library., 2019)
This poster aims to systematically review the effectiveness, achievements, lessons and challenges of maternal nutrition program in Nepal which implemented during the Millennium Development Goal (2000-2015) era with the technical and financial support from Micronutrient Initiative and UNICEF Nepal.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy